Photo‐Induced Halogen‐Atom Transfer: Generation of Halide Radicals for Selective Hydrohalogenation Reactions. Issue 43 (13th June 2022) - Geniller, Lilian; Taillefer, Marc; Jaroschik, Florian; Prieto, Alexis
Abstract: The first photo‐mediated process enabling the generation of halide radicals by Halogen‐Atom Transfer (XAT) is described. Contrary to radical transformations involving XAT reactivity, which exploit stable carbon radicals, this unique approach uses 1, 2‐dihaloethanes for the generation of unstable carbon radicals by XAT. These transient radicals then undergo β‐scission with release of ethylene and formation of more stable halide radicals which have been used in selective hydrohalogenations of a large number of unsaturated hydrocarbons, including Michael acceptors, unactivated alkenes and alkynes. This hydrohalogenation is tolerant of a broad range of functionalities and is believed to proceed through a radical‐chain manifold that propagates by the use of silane derivatives. Abstract : The first photo‐mediated process enabling the generation of halide radicals by halogen‐atom transfer (XAT) is described. This novel reactivity pattern relies on the use of 1, 2‐dihaloethanes for the generation of unstable carbon radicals by XAT, which after β‐scission, release halide radicals that have been used in selective hydrohalogenations of unsaturated hydrocarbons.